Adherence rate of quality‐of‐care indicators for Staphylococcus aureus bacteremia is extremely low in Japanese emergency and critical care departments: a multicenter retrospective observational study. Issue 2 (25th October 2017) - Miyamoto, Kyohei; Kato, Seiya; Kitayama, Junichi; Okawa, Junpei; Okamoto, Ayana; Kamei, Jun; Yoshiya, Kazuhisa; Asai, Hideki; Adachi, Shingo; Yukioka, Hidekazu; Akimoto, Hiroshi; Okuchi, Kazuo
Abstract : Aim: Staphylococcus aureus bacteremia causes significant morbidity and mortality and requires specific management to prevent complications. Most studies evaluating quality of care have been carried out in Europe and North America, and accurate epidemiological data are lacking in Asia. We aimed to describe the epidemiology and evaluate the quality of care for S. aureus bacteremia in Japan. Methods: From February 2011 to January 2014, we undertook a multicenter retrospective observational study in 10 departments of emergency and critical care in Japan. We included 118 hospitalized adult patients with S. aureus bacteremia and evaluated three quality‐of‐care indicators: follow‐up blood culture, treatment duration, and echocardiography. Results: The mean age of the patients was 63.5 ± 17.0 years. The major source of bacteremia was pneumonia ( n = 22, 19%), followed by skin and soft tissue infection ( n = 18, 15%). Thirty patients (25%) died in the hospital. Follow‐up blood culture was performed in 21/112 patients (19%). The duration of antimicrobial treatment was sufficient in 49/87 patients (56%). Echocardiography for patients with clinical indication was undertaken in 39/59 patients (66%). Any of the three indicators were inadequate in 101/118 (86%). Conclusion: The rate of adequate care for S. aureus bacteremia is low in Japan. The low adherence rate for follow‐up blood culture was particularly notable. Staphylococcus aureus bacteremia can be an important target of quality improvement interventions. Abstract : In this multicenter retrospective observational study, we evaluated the quality of care for Staphylococcus aureus bacteremia in Japan. This study revealed that most patients with S. aureus bacteremia (101/108; 86%) were treated inadequately.